Usability Analysis of Kahoot in Mathematics Education - dos Santos Teotônio, Lucas; Alves de Araújo, Aislânia; Soares dos Santos, Jucelio (RENOTE, 2021)
In this paper, we analyze the level of usability of Kahoot in the classroom context. For this, we select/adapt questions in the area of Mathematics, and its Technologies present in the “Exame Nacional do Ensino Médio” and, we apply these questions in a traditional way (paper-and-pencil) and in a gamified way through Kahoot. We elaborated/applied a survey to the participants to verify the level of usability of the instruments. As a result, the Kahoot tool demonstrated time savings, Ease of use, and promoted greater Satisfaction when comparing the application on paper-and-pencil. The participants considered the use of Kahoot to be more comfortable, exciting, satisfying, and encouraging learning better than the paper-and-pencil method.